2016
DOI: 10.1128/jvi.00946-16
|View full text |Cite
|
Sign up to set email alerts
|

The Influenza A Virus Genotype Determines the Antiviral Function of NF-κB

Abstract: The role of NF-B in influenza A virus (IAV) infection does not

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…We do not know whether the amplification resulted in the acquisition of additional adaptations. Titers of the virus stocks were determined by titration in MDCK II cells performed in triplicates, as described previously (69).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We do not know whether the amplification resulted in the acquisition of additional adaptations. Titers of the virus stocks were determined by titration in MDCK II cells performed in triplicates, as described previously (69).…”
Section: Methodsmentioning
confidence: 99%
“…Generation of recombinant SC35 and SC35M viruses. The pHW2000 plasmids containing the cloned segments of SC35 and SC35M (12) were transfected into a coculture of 293T/MDCK II cells (ratio 3:1) using Lipofectamine 2000 and further handled as described previously (69).…”
Section: Methodsmentioning
confidence: 99%
“…Although these clinical developments are promising, there are still open questions, mainly with regard to the mechanism of action-that is, the balance between virus-supportive NF-κB functions in the course of the virus life cycle and its antiviral activities by inducing robust inflammatory and antiviral responses. A recent study using genetic mouse knockouts of NF-κB transcription factors led to some controversial data about the consequences of complete versus partial inhibition of NF-κB functions for IV replication (Dam et al 2016). In addition, this study emphasized the importance of the viral genotype for susceptibility to the antiviral functions of NF-κB.…”
Section: Nuclear Factor κBmentioning
confidence: 96%
“…Upon activation, NF-κB translocates into the nucleus to induce expression of tumor necrosis factor alpha (TNF-α), IL-6, and IL-1β with multiple downstream effects, including inflammasome activation, apoptosis, and, importantly, further stimulation of NF-κB activation, which creates an inflammatory positive feedback loop. Despite clear evidence that NF-κB plays an important protective role in the immune response to influenza infection 116 and that impaired production of downstream cytokines, such as IL-6, can increase influenza-related mortality, 117 other studies have shown NF-κB can be “hijacked” to promote influenza replication, 118 , 119 resulting in some debate over its overall role in disease progression. 119 Inhibition of NF-κB has been suggested to be a possible treatment strategy for influenza infection.…”
Section: Molecular Mechanisms and Cellular Biologymentioning
confidence: 99%
“…Despite clear evidence that NF-κB plays an important protective role in the immune response to influenza infection 116 and that impaired production of downstream cytokines, such as IL-6, can increase influenza-related mortality, 117 other studies have shown NF-κB can be “hijacked” to promote influenza replication, 118 , 119 resulting in some debate over its overall role in disease progression. 119 Inhibition of NF-κB has been suggested to be a possible treatment strategy for influenza infection. 120 , 121 Although the role of NF-κB in SARS-CoV-2 has yet to be fully elucidated, the high levels of TNF-α and IL-6 in patients with severe COVID-19 infection are strongly suggestive of its activation.…”
Section: Molecular Mechanisms and Cellular Biologymentioning
confidence: 99%